Superb microvascular imaging for detecting carpal tunnel syndrome compared with power Doppler ultrasonography: A protocol for systematic review and meta-analysis. Issue 9 (5th March 2021) - Zhang, Jili; Zhu, Weikai; Lin, Mingxin; Jiang, Chang
Abstract: Background: Sonography enhances diagnostic accuracy by the detection of the epineural or intraneuronal blood flow.[1–4] Power Doppler ultrasonography (PDUS) in carpal tunnel syndrome (CTS) has been previously studied and shown to be valid and reliable for grading the intraneural flow.[3, 4] However, superb microvascular imaging (SMI) represents a new era in diagnostic sonography, and this new technology enables accurate visualization of vascular structures with intensive clutter suppression to provide flow signals for large to small vessels, and it presents these data at high frame rates.[5–7] Studies suggested that SMI is more sensitive in demonstrating blood flow in the diagnosis of CTS compared with PDUS.[7] In order to gain clarity, a meta-analysis to systematically review and synthesize relevant data on the evaluating intraneural blood flow of the median nerve (MN) using SMI and PDUS was undertaken. Methods: We will search PubMed, Web of Science, Cochrane Library, and Chinese biomedical databases from their inceptions to the December 31, 2020, without language restrictions. Two authors will independently carry out searching literature records, scanning titles and abstracts, full texts, collecting data, and assessing risk of bias. Review Manager 5.2 and Stata 14.0 software will be used for data analysis. Results: This systematic review will investigate whether superb microvascular imaging is more sensitive to display the blood flow in the MN with CTS than PDUS. Conclusion: Its findings will provide strong evidence for the feasibility of superb microvascular imaging on the detection of the neovascularization of the MN with CTS. Systematic review registration: INPLASY202110018.